Psychopathic killers: A meta-analytic review of the psychopathy-homicide nexus. (January 2019) - Fox, Bryanna; DeLisi, Matt
Abstract: Despite cultural notions that psychopathy and homicide are strongly linked, there has not been a quantitative meta-analytic review of the association between psychopathy and homicide offending. The current study meta-analyzed data from 29 unique samples from 22 studies that included 2603 homicide offenders, and found that the mean psychopathy score on the PCL-R for a homicide offender was 21.2 (95% CI = 18.9–23.6). This score is indicative of moderate psychopathy. The overall effect size r = 0.68 was large, and effect sizes intensified in studies of more severe manifestations of homicide including sexual homicide ( r = 0.71), sadistic homicide ( r = 0.78), serial homicide ( r = 0.74), and multi-offender homicide ( r = 0.80). Current study findings make clear that psychopathy and homicide are importantly linked and that psychopathic personality functioning is a significant risk factor for various forms of lethal violence.